Cr(VI) Reduction in aqueous solutions by siderite - Erdem, Mehmet; Gür, Faruk; Tümen, Fikret (My University, 2004)
Hexavalent chromium is a common and toxic pollutant in soils and wastewaters. Reduction of the mobile Cr(VI) to less mobile and less toxic Cr(III) is a solution for decontamination of industrial effluents. In this study, the reduction of hexavalent chromium in aqueous solutions by siderite was investigated. The influences of amount of acid, contact time, siderite dosage, initial Cr(VI) concentration, temperature and particle size of siderite have been tested in batch runs. The process was found to be acid, temperature and concentration dependent. The amount of acid is the most effective parameter affecting the Cr(VI) reduction since carbonaceous gangue minerals consume acid by side reactions. The highest Cr(VI) reduction efficiency (100%) occurred in the 50 mg/l Cr(VI) solution containing two times acid with respect to stoichiometric amount of Cr(VI) and at the conditions of siderite dosage 20 g/l, contact time 120 min and temperature 25 °C. Reduction efficiency increased with increase in temperature and decrease in particle size. The reduction capacity of siderite was found to be 17 mg-Cr(VI)/g.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hexavalent chromium; Reduction; Heavy metal; Siderite